Peran supervisi pendidikan dalam mengakselerasi kualitas pembelajaran di kelas - Isna Juwita Sari; Sri Mayang Mandra; Elvina Andriani Bugis; Syafaruddin (Journal of Practice Learning and Educational Development, 2026)
Digital transformation encourages educational institutions to adopt efficient, integrated, and responsive academic management systems. This research aims to examine academic management based on administrative efficiency, digital supervision, and staff coordination as effective academic management strategies in the digital era. The research approach uses qualitative methods with a library research design, involving the analysis of academic literature, scientific journals, and current educational policy documents (2020–2025). Data analysis was conducted thru thematic content analysis to understand the conceptual relationships between administrative efficiency, digital supervision, and staff coordination in shaping an adaptive and coordinated academic management system. The study results show that administrative efficiency accelerates data processing and reduces manual workload; digital supervision enables continuous data-based monitoring and feedback; while integrated staff coordination strengthens inter-unit collaboration and performance accountability. The integration of these three aspects creates a synergistic, adaptive, and responsive academic management system to digital challenges, thereby supporting the overall effectiveness of academic governance. This research provides a theoretical contribution to expanding the understanding of digital-based academic management and practical implications for educational institution managers in designing efficient, collaborative, and adaptive academic systems.